1761. Effect of Carbapenem-Resistant Enterobacteriaceae (CRE) Surveillance Case Definition Change on CRE Epidemiology—Selected US Sites, 2015–2016. (26th November 2018) - Duffy, Nadezhda; Bulens, Sandra N; Reses, Hannah; Karlsson, Maria S; Ansari, Uzma; Bamberg, Wendy; Janelle, Sarah J; Jacob, Jesse T; Bower, Chris; Wilson, Lucy E; Vaeth, Elisabeth; Lynfield, Ruth; et al.
Abstract: Background: Carbapenem-resistant Enterobacteriacae (CRE) are an urgent US public health threat. CDC reported CRE incidence to be 2.93/100, 000 population in 2012–2013 in selected sites but changed the CRE surveillance case definition in 2016 to improve sensitivity for detecting carbapenemase-producing (CP) CRE. We describe CRE epidemiology before and after the change. Methods: Eight CDC Emerging Infections Program sites (CO, GA, MD, MN, NM, NY, OR, TN) conducted active, population-based CRE surveillance in selected counties. A case was defined as having an isolate of E. coli, Enterobacter, or Klebsiella meeting a susceptibility phenotype (figure) at a clinical laboratory from urine or a normally sterile body site in a surveillance area resident in a 30-day period. We collected data from medical records and defined cases as community-associated (CA) if no healthcare risk factors were documented. A convenience sample of isolates were tested for carbapenemase genes at CDC by real-time PCR. We calculated incidence rates (per 100, 000 population) by using US Census data. Case epidemiology and the proportion of CP-CRE isolates in 2015 versus 2016 were compared. Results: In total, 442 incident CRE cases were reported in 2015, and 1, 149 cases were reported in 2016. Most isolates were cultured from urine: 87% in 2015 and 92% in 2016 ( P < .001). The crude overall pooled mean incidence in 2015 was 2.9 (range by site: 0.45–7.19) and in 2016 was 7.48 (range: 3.13–15.95). The most common CRE genus was Klebsiella (51%) in 2015, and in 2016 was Enterobacter (41%, P < 0.001). Of the subset of CRE isolates tested at CDC, 109/227 (48%) were CP-CRE in 2015 and 109/551 (20%) were CP-CRE in 2016. In 2015, 52/442 (12%) of cases were CA CRE, and in 2016, 267/1, 149 (23%) were CA CRE ( P < 0.001). In 2016, 3/111 (2.7%) of CA CRE isolates tested were CP-CRE. Conclusion: A large increase in reported CRE incidence was observed after the change in the case definition. The new case definition includes a substantially larger number of Enterobacter cases. A decrease in CP-CRE prevalence appears to be driven by an increase in non-CP-CRE cases. Although CP-CRE in the community still appear to be rare, a substantial proportion of phenotypic CRE appear to be CA, and CDC is undertaking efforts to further investigate CA CRE, including CP-CRE. Disclosures: G. Dumyati, Seres: Scientific Advisor, Consulting fee.